1997
DOI: 10.1128/iai.65.3.882-889.1997
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity with a specific epitope of outer surface protein A predicts protection from infection with the Lyme disease spirochete, Borrelia burgdorferi

Abstract: The response to recombinant vaccines for Lyme disease was studied to determine serum antibody levels effective in protecting against tick-transmitted infection. Data presented here demonstrate a significant correlation between antibody to an epitope on outer surface protein A (OspA) and protection against infection with Borrelia burgdorferi in canines and mice. A competitive enzyme-linked immunosorbent assay was developed to measure antibody to a site on OspA, defined by monoclonal antibody LA-2. Comparison of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…The obtained protection data also indicate that our design maintains the protective epitope characterized for OspA serotype 1 by the monoclonal antibody LA-2 [7] . An immune response to this epitope was shown to correlate with protection in a dog model of infection [18] and it was also shown in the LYMErix phase III clinical trial that the LA-2 equivalent antibody levels were lower in sera from breakthrough cases [52] . By focusing only on the C-terminal part of OspA, our LB-vaccine also possesses a higher molar ratio of potentially protective epitopes compared to a vaccine using the full-length OspA, which might be favorable since a low vaccine dose could still be effective in generating protective immunity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The obtained protection data also indicate that our design maintains the protective epitope characterized for OspA serotype 1 by the monoclonal antibody LA-2 [7] . An immune response to this epitope was shown to correlate with protection in a dog model of infection [18] and it was also shown in the LYMErix phase III clinical trial that the LA-2 equivalent antibody levels were lower in sera from breakthrough cases [52] . By focusing only on the C-terminal part of OspA, our LB-vaccine also possesses a higher molar ratio of potentially protective epitopes compared to a vaccine using the full-length OspA, which might be favorable since a low vaccine dose could still be effective in generating protective immunity.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that antibodies targeting the C-terminal part of OspA play a crucial role in protection [18] . Subsequently, it has been shown that a vaccine based on the C-terminal half of OspA from B. burgdorferi (constituting approximately 55% of the full-length protein) partially protected mice against a homologous challenge [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the bactericidal antigen binding fragments (Fabs) H6831 and monoclonal antibody CB2 recognize the C-terminal fragment of B. burgdorferi OspB (4, 8, 12). Thus, the C-termini of the lipoproteins of Lyme disease borreliae Osps may stimulate targeting antibodies in the hosts (13,14,16,36). It is considered that the C-termini of the Vmp protein family of relapsing fever borreliae may be predominant B-cell epitopes for antibodies on these regions.…”
Section: Discussionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention has estimated that >300 000 Americans receive a diagnosis of Lyme disease yearly [1]. Antibodies raised against Borrelia outer surface protein A (OspA) block transmission of spirochetes from ticks to vertebrate hosts in animal models [2][3][4]. Based on the effectiveness of OspA-specific humoral immunity in these animal models, vaccines containing recombinant OspA of B. burgdorferi were developed to induce a similar antibody response in humans for the prevention of Lyme disease [5].…”
mentioning
confidence: 99%